Algunas cuestiones de arqueología de al-Andalus - Gómez Martínez, Susana (2020)
Juan Zozaya expressed great appreciation for the Garb al-Andalus and Portugal. Its cosmopolitan vocation was linked to a history of al-Andalus prior the medieval peninsular kingdoms and the current border between Spain and Portugal. Reciprocally, researchers about the Islamic period in Portugal felt great esteem for the teacher who contributed so much to the advancement of research in the Gharb. There are few overall visions about the western territories of al-Andalus from an archaeological perspective. It is an audacity on my part to pretend to make a synthesis on such a broad territory and with such a long chronological scope in so few lines. What I propose is a reflexion on some questions of the evolution of the Garb to encourage discussion. One of the main ones is related to the marginal character of the Garb, but also about the peculiarities of its settlement, or the features of archaism in diverse expressions of the material culture.